2014
DOI: 10.1016/j.atherosclerosis.2014.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low extracellular pH on NF-κB activation in macrophages

Abstract: ObjectiveMany diseases, including atherosclerosis, involve chronic inflammation. The master transcription factor for inflammation is NF-κB. Inflammatory sites have a low extracellular pH. Our objective was to demonstrate the effect of pH on NF-κB activation and cytokine secretion.MethodsMouse J774 macrophages or human THP-1 or monocyte-derived macrophages were incubated at pH 7.0–7.4 and inflammatory cytokine secretion and NF-κB activity were measured.ResultsA pH of 7.0 greatly decreased pro-inflammatory cytok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 53 publications
1
21
1
Order By: Relevance
“…Bellocq et al ( 45 ) have shown that 2 h culture in medium adjusted to pH 7.0 activates nuclear factor (NF)-B, the key inducer of proinfl ammatory cytokine expression in rat and mouse macrophages via a positive feedback loop of TNF-␣ secretion and autocrine signaling. In contrast, other studies have shown that low pH (pH 7.0-5.5) inhibits LPS-induced TNF-␣ secretion (mediated by NF-B) in mouse and rabbit, but not in human macrophages (46)(47)(48)(49). Accordingly, an inhibitory effect by low pH on LPS-induced NF-B signaling was found in mouse, but not in human macrophages ( 46,49 ).…”
Section: Acidic Extracellular Ph Increases the Retention Of Atherogencontrasting
confidence: 42%
See 2 more Smart Citations
“…Bellocq et al ( 45 ) have shown that 2 h culture in medium adjusted to pH 7.0 activates nuclear factor (NF)-B, the key inducer of proinfl ammatory cytokine expression in rat and mouse macrophages via a positive feedback loop of TNF-␣ secretion and autocrine signaling. In contrast, other studies have shown that low pH (pH 7.0-5.5) inhibits LPS-induced TNF-␣ secretion (mediated by NF-B) in mouse and rabbit, but not in human macrophages (46)(47)(48)(49). Accordingly, an inhibitory effect by low pH on LPS-induced NF-B signaling was found in mouse, but not in human macrophages ( 46,49 ).…”
Section: Acidic Extracellular Ph Increases the Retention Of Atherogencontrasting
confidence: 42%
“…In contrast, other studies have shown that low pH (pH 7.0-5.5) inhibits LPS-induced TNF-␣ secretion (mediated by NF-B) in mouse and rabbit, but not in human macrophages (46)(47)(48)(49). Accordingly, an inhibitory effect by low pH on LPS-induced NF-B signaling was found in mouse, but not in human macrophages ( 46,49 ). Differences in the study setups and the pH range used likely explain the contrasting results obtained in mouse macrophages.…”
Section: Acidic Extracellular Ph Increases the Retention Of Atherogenmentioning
confidence: 68%
See 1 more Smart Citation
“…The oxidized linoleic acid metabolite 13-Shydroxyoctadecadienoic acid (13-HODE) was observed in human prostate adenocarcinoma specimens, whereas adjacent normal tissue showed no immunoreactivity for 13-HODE [57]. Similarly, a low pH in the extracellular milieu, another activator of TRPV1 [58], is also associated with inflammation and the cancer microenvironment [59,60]. LNCaP cells produce high amounts of 20-hydroxyeicosatetraeonic acid (20-HETE) [61], another endogenous activator of TRPV1 channels [62].…”
Section: Discussionmentioning
confidence: 99%
“…The expression of adhesion molecules can be induced by pro-inflammatory cytokines such as TNF-α and IL-1, both of which up-regulate leukocyte adhesion molecules in an NF-κB-dependent process (46). A recent study by Gerry et al showed that a modest decrease in extracellular pH (pH of 7.0) can have marked effects on NF-κB activation and cytokine secretion in macrophages (47). Atherosclerotic lesions, as well as other sites of chronic inflammation, such as rheumatoid joints and tumors, have areas of low extracellular pH.…”
Section: Inflammatory Chemokines and Cytokines In The Pathogenesismentioning
confidence: 99%